ATOMS: ALMA Three-millimeter Observations of Massive Star-forming regions – I. Survey description and a first look at G9.62+0.19. Issue 3 (6th June 2020) - Liu, Tie; Evans, Neal J; Kim, Kee-Tae; Goldsmith, Paul F; Liu, Sheng-Yuan; Zhang, Qizhou; Tatematsu, Ken'ichi; Wang, Ke; Juvela, Mika; Bronfman, Leonardo; Cunningham, Maria R; Garay, Guido; et al.
ABSTRACT: The ATOMS, standing for ALMA Three-millimeter Observations of Massive Star-forming regions, survey has observed 146 active star-forming regions with ALMA band 3, aiming to systematically investigate the spatial distribution of various dense gas tracers in a large sample of Galactic massive clumps, to study the roles of stellar feedback in star formation, and to characterize filamentary structures inside massive clumps. In this work, the observations, data analysis, and example science of the ATOMS survey are presented, using a case study for the G9.62+0.19 complex. Toward this source, some transitions, commonly assumed to trace dense gas, including CS J  = 2−1, HCO + J  = 1−0, and HCN J  = 1−0, are found to show extended gas emission in low-density regions within the clump; less than 25 per cent of their emission is from dense cores. SO, CH3 OH, H 13 CN, and HC3 N show similar morphologies in their spatial distributions and reveal well the dense cores. Widespread narrow SiO emission is present (over ∼1 pc), which may be caused by slow shocks from large–scale colliding flows or H ii regions. Stellar feedback from an expanding H ii region has greatly reshaped the natal clump, significantly changed the spatial distribution of gas, and may also account for the sequential high-mass star formation in the G9.62+0.19 complex. The ATOMS survey data can be jointly analysed with other survey data, e.g. MALT90, Orion B, EMPIRE, ALMA_IMF, and ALMAGAL, to deepen our understandings of 'dense gas' star formation scaling relations and massive protocluster formation.